KONTROL LAMPU GEDUNG MELALUI WIFI ESP8266 DENGAN WEB SERVER LOKAL - Prasetyo Adi Nugroho (Institut Teknologi dan Bisnis Swadharma, 2021)
This study aims to design a Building Automation System that can control electrical devices that are carried out remotely at the same location or via WiFi and Web Server applications, to make it easier for people to control devices located in distant buildings without direct contact and can be accessed. anywhere within range of the local network. The research method used is research and development methods, namely by conducting literature studies and interviews with electrical and arduino experts. The results of the research are a system made using the ESP8266 WiFi module which is set as a station, which connects Arduino to the local internet which will be controlled by the Web Sever application from anywhere with local internet connection range. The Building Automation System that is made can switch Hologen lamps and incandescent lamps and is set using the blynk application that is connected to an internet connection.